Vous êtes sur la page 1sur 1

# The Theoretical Minimum – Classical Mechanics – Exercise L11.

4
𝟏 𝒆 𝒆
𝑯 = ∑{ [𝒑𝒊 − 𝑨𝒊 (𝒙)] [𝒑𝒊 − 𝑨𝒊 (𝒙)]}
𝟐𝒎 𝒄 𝒄
𝒊

Using the above Hamiltonian, work out Hamilton’s equations of motion and show that you just get
back to the Newton-Lorentz equation of motion.

## First we write the Hamiltonian in a more explicit form.

1 𝑒 𝑒 1 𝑒 𝑒 1 𝑒 𝑒
𝐻= (𝑝𝑥 − 𝐴𝑥 ) (𝑝𝑥 − 𝐴𝑥 ) + (𝑝𝑦 − 𝐴𝑦 ) (𝑝𝑦 − 𝐴𝑦 ) + (𝑝𝑧 − 𝐴𝑧 ) (𝑝𝑧 − 𝐴𝑧 )
2𝑚 𝑐 𝑐 2𝑚 𝑐 𝑐 2𝑚 𝑐 𝑐
𝜕𝐻
Now we use the definition 𝑞̇ = explicitly for the three dimensional components.
𝜕𝑝

𝜕𝐻 2 𝑒 1 𝑒 𝑒
𝑥̇ = = (𝑝𝑥 − 𝐴𝑥 ) = (𝑝𝑥 − 𝐴𝑥 ) ⇔ 𝑚𝑥̇ = (𝑝𝑥 − 𝐴𝑥 )
𝜕𝑝𝑥 2𝑚 𝑐 𝑚 𝑐 𝑐
𝜕𝐻 2 𝑒 1 𝑒 𝑒
𝑦̇ = = (𝑝𝑦 − 𝐴𝑦 ) = (𝑝𝑦 − 𝐴𝑦 ) ⇔ 𝑚𝑦̇ = (𝑝𝑦 − 𝐴𝑦 )
𝜕𝑝𝑦 2𝑚 𝑐 𝑚 𝑐 𝑐
𝜕𝐻 2 𝑒 1 𝑒 𝑒
𝑧̇ = = (𝑝𝑧 − 𝐴𝑧 ) = (𝑝𝑧 − 𝐴𝑧 ) ⇔ 𝑚𝑧̇ = (𝑝𝑧 − 𝐴𝑧 )
𝜕𝑝𝑧 2𝑚 𝑐 𝑚 𝑐 𝑐
−𝜕𝐻
We continue with 𝑝̇ = for the x component and use the above results to plug in on the way.
𝜕𝑞

## −𝜕𝐻 1 𝑒 𝑒 𝜕𝐴𝑥 1 𝑒 𝑒 𝜕𝐴𝑦 1 𝑒 𝑒 𝜕𝐴𝑧

𝑝̇𝑥 = = (𝑝𝑥 − 𝐴𝑥 ) + (𝑝𝑦 − 𝐴𝑦 ) + (𝑝𝑧 − 𝐴𝑧 )
𝜕𝑥 𝑚 𝑐 𝑐 𝜕𝑥 𝑚 𝑐 𝑐 𝜕𝑥 𝑚 𝑐 𝑐 𝜕𝑥
1 𝑒 𝑒 𝜕𝐴𝑥 𝑒 𝜕𝐴𝑦 𝑒 𝜕𝐴𝑧
= [(𝑝𝑥 − 𝐴𝑥 ) + (𝑝𝑦 − 𝐴𝑦 ) + (𝑝𝑧 − 𝐴𝑧 ) ]
𝑚 𝑐 𝑐 𝜕𝑥 𝑐 𝜕𝑥 𝑐 𝜕𝑥

## 1 𝑒 𝜕𝐴𝑥 𝜕𝐴𝑦 𝜕𝐴𝑧

= (𝑚𝑥̇ + 𝑚𝑦̇ + 𝑚𝑧̇ )
𝑚 𝑐 𝜕𝑥 𝜕𝑥 𝜕𝑥

## 𝑒 𝜕𝐴𝑥 𝜕𝐴𝑦 𝜕𝐴𝑧

= (𝑥̇ + 𝑦̇ + 𝑧̇ )
𝑐 𝜕𝑥 𝜕𝑥 𝜕𝑥

With this result we get back to 𝑚𝑥̇ and take its time derivative.
𝑑 𝑑 𝑒 𝑒 𝑑𝐴𝑥 𝑒 𝜕𝐴𝑥 𝜕𝐴𝑥 𝜕𝐴𝑥
𝑚𝑥̇ = (𝑝𝑥 − 𝐴𝑥 ) = 𝑝̇𝑥 − = 𝑝̇𝑥 − ( 𝑥̇ + 𝑦̇ + 𝑧̇ )
𝑑𝑡 𝑑𝑡 𝑐 𝑐 𝑑𝑡 𝑐 𝜕𝑥 𝜕𝑦 𝜕𝑧
𝑒 𝜕𝐴𝑥 𝜕𝐴𝑦 𝜕𝐴𝑧 𝑒 𝜕𝐴𝑥 𝜕𝐴𝑥 𝜕𝐴𝑥
⇔ 𝑚𝑥̈ = (𝑥̇ + 𝑦̇ + 𝑧̇ )− ( 𝑥̇ + 𝑦̇ + 𝑧̇ )
𝑐 𝜕𝑥 𝜕𝑥 𝜕𝑥 𝑐 𝜕𝑥 𝜕𝑦 𝜕𝑧

## 𝑒 𝜕𝐴𝑦 𝜕𝐴𝑥 𝑒 𝜕𝐴𝑧 𝜕𝐴𝑥

⇔ 𝑚𝑥̈ = ( − ) 𝑦̇ + ( − ) 𝑧̇
𝑐 𝜕𝑥 𝜕𝑦 𝑐 𝜕𝑥 𝜕𝑧
𝑒
⇔ 𝑚𝑥̈ = (𝐵𝑧 𝑦̇ − 𝐵𝑦 𝑧̇ )
𝑐
This is the Newton-Lorentz equation of motion for the 𝑥 component of the system.
We will get analogous results for the 𝑦 and 𝑧 components, by calculating 𝑚𝑦̈ and 𝑚𝑧̈ .

## Filip Van Lijsebetten 14/11/2014

filipvl@vanlijsebetten.be